To study optimum parameters in the soap production derived from palm kernel oil and palm oil by saponification - Rafiqa Liyana, Rahimi (2013)
Manufacture of soaps from distilled fatty acids of palm kernel oil (PKO) and palm oil (PO) is a well-established technology in Malaysia. In this research, the production of soap from palm kernel oil is by direct saponification fats and oils and it is evaluated for moisture content (%), water hardness, emulsifying properties, pH value, and foamability of soap .The objective of this research is to study the production of soap from palm kernel oil (PKO). This is because of palm oil (PO) and palm kernel oil (PKO) as raw material have important fatty acids involved in soap making which are C16-C18 and C12-C14 which contribute to the detergency properties, lathering and washing properties of the soaps. Parameters that involve in this research are ratio concentration of raw materials, temperature and speed. For the concentration, the ratio is from 0 until 100 %, for the temperature the best range is from 20˚C- 70˚C, for the speed the best range is from 600- 1500 rpm, and within constant the time of process which is 30 min. This experiment consists only one process which is reactions process. First step is the temperature, speed and time of raw material are set as stated in the table. Second step is palm oil and palm kernel oil are mixed together on the hot plate. Then the sodium hydroxide (NaOH) is added gradually together with the sodium chloride (NaCl) and EDTA based on the amount stated in table. The study has shown that the relationship of all parameter with optimum condition is achieved in order to produce high yield production of soap and in good quality compared with the production of soap from tallow and coconut oil. The optimum concentration in manufacturing of soap is making from a blend of 80% palm kernel and 20% palm oil with the speed 900 rpm at temperature 30˚ C .